2010
DOI: 10.3928/01477447-20100429-15
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Gas Exchange Impairment Following Tourniquet Deflation: A Prospective, Single-Blind Clinical Trial

Abstract: The tourniquet has been considered as a recognized cause of limb ischemia/reperfusion injury in orthopedic surgery resulting in a transient neutrophil, monocyte activation, and enhanced neutrophil transendothelial migration with potential remote tissue injury. This study investigated the effect of unilateral tourniquet application within a safe time limit on pulmonary function and the roles of lipid peroxidation and systemic inflammatory response. Thirty patients undergoing unilateral lower extremity surgery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…The a/A ratio, A-aO 2 , and respiratory index can be used to assess pulmonary gas exchange. We found that the a/A ratio, A-aO 2 , and respiratory index were significantly decreased at 6 h after tourniquet release, implying that gas exchange in the lungs was impaired, similar to our findings from a previous study [ 10 ]. In addition, we found that these indices were improved by TEAS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The a/A ratio, A-aO 2 , and respiratory index can be used to assess pulmonary gas exchange. We found that the a/A ratio, A-aO 2 , and respiratory index were significantly decreased at 6 h after tourniquet release, implying that gas exchange in the lungs was impaired, similar to our findings from a previous study [ 10 ]. In addition, we found that these indices were improved by TEAS.…”
Section: Discussionsupporting
confidence: 91%
“…This condition may be much more important in orthopedic procedures in which tourniquet-related ischemia-reperfusion damage develops and the lung gets injured [ 9 ]. Our previous research showed that tourniquet-induced lung injury was correlated with impaired gas exchange and that inflammation factors such as interleukin-1 (IL-1), interleukin-6 (IL-6), and tumor necrosis factor- α (TNF- α ) are important mediators of this effect [ 10 ]. This suggests that reducing the inflammatory response should have a positive effect on postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Tourniquets may increase blood pressure, probably because of autonomous nervous system changes ( 74 ) and, especially, in children, it may induce hyperthermia. Pulmonary gas exchange disorder may occur a few hours after tourniquet deflation and in the safe time limit of tourniquet time ( 75 ). After deflation pulse and end tidal Co 2 increases to reach a peak after 5 minutes and after 15 minutes returns to the normal range.…”
Section: Resultsmentioning
confidence: 99%
“…Measures of atrophy, strength and functional mobility were not performed (38). The remainder of studies cited were conducted with younger adults during and after ACL reconstruction (6), with meniscectomy patients (39), with young patients having ORIF (19), and with subjects requiring surgery for femoral shaft fractures (control group) and tibial and ankle fractures (tourniquet group) (24) that reported changes in measures of pulmonary function.…”
Section: Introductionmentioning
confidence: 99%